Biodegradation of Quinoline by Hydrogel Beads of Activated Sludge in the Air-Lift Bioreactor - Ahmed Khudhair, Haneen; ., . (International Journal of Engineering and Technology, 2018)
Quinoline is a nitrogen heterocyclic compound (NHC) with a molecular formula of C9H7N. Microbial degradation of quinoline occurs under both aerobic and anaerobic conditions. In this study, the aerobic biodegradation of quinoline was investigated with activated sludge which was taken from a municipal sewage wastewater treatment plant in the air-lift bioreactor (ALBR).The activated sludge was entrapped in poly-vinyl-alcohol-calcium alginate (PVA-Ca alginate) hydrogel beads. The optimal conditions for microbial cells entrapment, such as Ca-alginate concentration, biomass concentration in the hydrogel bead and bead size, were determined with concerning to improve the quinoline degradation rate. Also, the initial quinoline concentration was determined. The optimum temperature and initial pH for quinoline degradation were 30°C and pH 7–8, respectively. During the biodegradation process, the culture broth became yellow and brown in turn, which indicated that several intermediates were generated. The results showed that the diversity of microbial cells improves and accelerates the quinoline biodegradation. The repeated use of the hydrogel beads for quinoline degradation was performed and the results revealed that the beads were active and intact up to 4 successive cycles without breakage or loss their stability in the continuous mode. Thus, (PVA-Ca alginate) hydrogel beads have great potential to be a matrix for the cell immobilization in quinoline biodegradation. The various initial concentrations of quinoline (50, 100, 250, and 500mg/L) were completely degraded in batch-mode experiments; under optimal conditions: PVA conc., 80%w/v; calcium alginate conc., 20%w/v; initial biomass concentration the hydrogel bead, 3mL / 10 mL of gel solution; and the hydrogel bead size, about 3mm in diameter, at different time intervals (4, 6, 10, and 14h), respectively.